Functional Analysis of Missense Mutations of OAT, Causing Gyrate Atrophy of Choroid and Retina. Issue 1 (17th October 2012) - Doimo, Mara; Desbats, Maria Andrea; Baldoin, Maria Cristina; Lenzini, Elisabetta; Basso, Giuseppe; Murphy, Elaine; Graziano, Claudio; Seri, Marco; Burlina, Alberto; Sartori, Geppo; Trevisson, Eva; Salviati, Leonardo
ABSTRACT We studied eight kindreds with gyrate atrophy of choroid and retina (GA), a rare autosomal recessive disorder caused by mutations of the OAT gene, encoding the homoexameric enzyme ornithine‐delta‐aminotransferase. We identified four novel and five previously reported mutations. Missense alleles were expressed in yeast strain carrying a deletion of the orthologous of human OAT. All mutations markedly reduced enzymatic activity. However, the effect on the yeast growth was variable, suggesting that some mutations retain residual activity, below the threshold of the enzymatic assay. Mutant proteins were either highly unstable and rapidly degraded, or failed to assemble to form the active OAT hexamer. Where possible, fibroblast analysis confirmed these data. We found no correlation between the residual enzymatic activity and the age of onset, or the severity of symptoms. Moreover, the response to B6 was apparently not related to the specific mutations carried by patients. Overall these data suggest that other factors besides the specific OAT genotype modulate (GA) phenotype in patients. Finally, we found that 5‐aminoimidazole‐4‐carboxamide ribonucleoside (AICAR), an AMPK activator known to increase mitochondrial biogenesis, markedly stimulates OAT expression, thus representing a possible treatment for a subset of GA patients with hypomorphic alleles.